The Great Cross-Border Bank Deleveraging : Supply Constraints and Intra-Group Frictions - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2014)
International banks greatly reduced their direct cross-border and local affiliates' lending as the global financial crisis strained balance sheets, lowered borrower demand, and changed government policies. Using bilateral, lender-borrower countrydata and controlling for credit demand, we show that reductions largely varied in line with markets' prior assessments of banks' vulnerabilities, with banks' financial statement variables and lender-borrower country characteristics playing minor roles. We find evidence that moving resources within banking groups became more restricted as drivers of reductions in direct cross-border loans differ from those for local affiliates' lending, especially for impaired banking systems. Home bias induced by government interventions, however, affected both equally.